2009
DOI: 10.1111/j.1744-7348.2008.00288.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sowing date and straw mulch on virus incidence and aphid infestation in organically grown faba beans (Vicia faba)

Abstract: The effect of sowing date on aphid infestation and the incidence of aphid-transmitted viruses were investigated in organically managed, small-scale field experiments with two faba bean cultivars over 3 years . As an additional factor, straw mulch was applied in 2 of the 3 years shortly before the start of vector activity in May. Virus incidence was determined using enzyme-linked immunosorbent assay and immunoelectron microscopy. Aphid flight activity was monitored using standard yellow water traps. Bean coloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
0
5
1
Order By: Relevance
“…In this study A. gossypii first appeared at the seedling stage, sucking the plant sap, leaving the leaves curled and wrinkled which were mostly observed on the control plots with similar finding made by Brust (2008). Results from this study and studies by Saucke et al (2009) have indicated that mulches have no significant effect on aphid colonisation. This may be due to fact that straw and other mulching materials used in this study probably do not exhibit pest-repellent properties.…”
Section: Impact Of Mulching Materials On the Mean Score And The Numbecontrasting
confidence: 48%
“…In this study A. gossypii first appeared at the seedling stage, sucking the plant sap, leaving the leaves curled and wrinkled which were mostly observed on the control plots with similar finding made by Brust (2008). Results from this study and studies by Saucke et al (2009) have indicated that mulches have no significant effect on aphid colonisation. This may be due to fact that straw and other mulching materials used in this study probably do not exhibit pest-repellent properties.…”
Section: Impact Of Mulching Materials On the Mean Score And The Numbecontrasting
confidence: 48%
“…For example, it is recommended to sow early so the plants are well developed before aphids start to colonise the crop. However, in a study on faba beans in Germany, aphid infestation was not consistently reduced through early sowing; nevertheless early sowing resulted in lower virus incidence, possibly because of stronger mature plant resistance in the early-than in the late-sown beans (Saucke et al 2009). While grain legumes grown to maturity are typically sown in the spring or autumn, summer sowing is possible if they are used as cover crops.…”
Section: Sowing and Inoculationmentioning
confidence: 95%
“…The effects of feeding by A. pisum is the reduction of yield resulting from sap sucking. The pest can also contribute to the spread of viral diseases (Saucke et al, 2009). NDVI index so far was used to asses both infestation of plants by aphids and the impact of nutrient deficiencies on the condition of plants, however, these factors were analyzed separately.…”
Section: Introductionmentioning
confidence: 99%